2020
DOI: 10.3389/fped.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

Using Platelet Parameters to Anticipate Morbidity and Mortality Among Preterm Neonates: A Retrospective Study

Abstract: Background: Platelets participate in many physiological and pathological functions and some platelet parameters predict adult diseases. However, few studies report whether platelet parameters may reflect neonatal disease and mortality in a large cohort.Objective: We aimed to investigate whether platelet parameters could predict bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), intraventricular hemorrhage (IVH), and NICU mortality. Study Design and Methods:This retrospective cohort study examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
2
19
2
Order By: Relevance
“…This study showed that platelet counts are significantly lower in infants developing BPD and in rats with experimental BPD induced by hyperoxia. This finding is in line with a study by Okur et al who reported a lower PLT and PMI in BPD infants during the first week of life (15), but is not supported by Go et al who report that platelet parameters at birth were not associated with BPD after multivariate analysis (16). This difference might be due to the different timing of these studies.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that platelet counts are significantly lower in infants developing BPD and in rats with experimental BPD induced by hyperoxia. This finding is in line with a study by Okur et al who reported a lower PLT and PMI in BPD infants during the first week of life (15), but is not supported by Go et al who report that platelet parameters at birth were not associated with BPD after multivariate analysis (16). This difference might be due to the different timing of these studies.…”
Section: Discussionsupporting
confidence: 87%
“…Since large platelets are more reactive than small platelets, an elevated platelet size (i.e., a high MPV) is considered a marker of platelet activation ( 56 , 57 ). Elevated MPV has been associated with cardiovascular disease in adults ( 58 ) and several studies have analyzed the association between MPV and complications of prematurity such as bronchopulmonary dysplasia, sepsis, intraventricular hemorrhage, retinopathy of prematurity, or PDA ( 59 63 ). Nevertheless, our meta-analysis could not demonstrate an association between MPV and hsPDA ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have focused on the relationship between MPV and the mortality of neonatal, especially premature neonates. Go et al [ 24 ] found that MPV ≥10.2 fL correlates with mortality among neonates born after <32 weeks’ gestation. Hebatallah [ 25 ] found that day 3 MPV can be used as a surrogate marker for the prediction of early-onset sepsis and associated mortality in preterm neonates.…”
Section: Discussionmentioning
confidence: 99%